CS12192, a Novel JAK3/JAK1/TBK1 Inhibitor, Synergistically Enhances the Anti-Inflammation Effect of Methotrexate in a Rat Model of Rheumatoid Arthritis - Fang, Zhengyu; Hu, Yiping; Dai, Jiajing; He, Lianhua; He, Juan; Xu, Bihua; Han, Xinle; Zhong, Fubo; Lan, Huiyao; Wang, Qingwen (International journal of molecular sciences, 2022)
Rheumatoid arthritis (RA) is a common disease worldwide and is treated commonly with methotrexate (MTX). CS12192 is a novel JAK3 inhibitor discovered by Chipscreen Biosciences for the treatment of autoimmune diseases. In the present study, we examined the therapeutic effect of CS12192 against RA and explored if the combinational therapy of CS12192 and MTX produced a synergistic effect against RA in rat collagen-induced arthritis (CIA). Arthritis was induced in male Sprague-Dawley rats by two intradermal injections of bovine type II collagen (CII) and treated with MTX, CS12192, or the combination of CS12192 and MTX daily for two weeks. Effects of different treatments on arthritis score, X-ray score, pathology, and expression of inflammatory cytokines and biomarkers were examined. We found that treatment with either CS12192 or MTX produced a comparable therapeutic effect on CIA including: (1) significantly lowering the arthritis score, X-ray score, serum levels of rheumatic factor (RF), C-reactive protein (CRP), and anti-nuclear antibodies (ANA); (2) largely alleviating histopathological damage, reducing infiltration of Th17 cells while promoting Treg cells; (3) inhibiting the expression of inflammatory cytokines and chemokines such as IL-1β, TNF-α, IL-6, CCL2, and CXCL1. All these inhibitory effects were further improved by the combinational therapy with MTX and CS12192. Of importance, the combinational treatment also resulted in a marked switching of the Th17 to Treg and the M1 to M2 immune responses in synovial tissues of CIA. Thus, when compared to the monotherapy, the combination treatment with CS12192 and MTX produces a better therapeutic effect against CIA with a greater suppressive effect on T cells and macrophage-mediated joint inflammation.